Pelatihan Pembelajaran Melalui Microsoft Office 365 Untuk Guru Madrasah Aliyah Al-Asy’ari Keras - Kamilah, Ria; Ma’rifatulloh, Sayid; Laili, Elisa Nurul; Fajarina, Maskhurin (Fakultas Tarbiyah IAIN Kediri, 2024)
Technology skill is needed very much especially for intergrating technology in teaching and learning. However, PKM team found that the technology skills of the teachers of Madrasah Aliyah Al-Asy’ari Keras are still less. Their teaching and learning focuses on boards and papers so that the students feel bored. These problems inspire PKM team of English Language Education Department of UHASY to carry out training on teaching and learning through microsoft office 365 in that school. This training is to add the technology skill of the teachers in order to be applied in their class to make their teaching becomes more interesting and challenging. Meanwhile, the method of this PKM is by doing training for 33 hours, 18 hours of offline and online for 15 hours. After two days of offline training, it can be known that the teachers of MA get new knowledge about microsft office 365 and 37% of them (10 young teachers) can operate office 365 well based on the observation result of PKM team. These ten young teachers are also active in online training. In deed, the training of teaching and learning through office 365 helps the teachers when they cannot come to teach at school.